Genetic Diversity in Passiflora Species Assessed by Morphological and ITS Sequence Analysis - Shiamala Devi Ramaiya; Japar Sidik Bujang; Muta Harah Zakaria (The Scientific World Journal)
This study used morphological characterization and phylogenetic analysis of the internal transcribed spacer (ITS) region of nuclear ribosomal DNA to investigate the phylogeny of Passiflora species. The samples were collected from various regions of East Malaysia, and discriminant function analysis based on linear combinations of morphological variables was used to classify the Passiflora species. The biplots generated five distinct groups discriminated by morphological variables. The group consisted of cultivars of P. edulis with high levels of genetic similarity; in contrast, P. foetida was highly divergent from other species in the morphological biplots. The final dataset of aligned sequences from nine studied Passiflora accessions and 30 other individuals obtained from GenBank database (NCBI) yielded one most parsimonious tree with two strongly supported clades. Maximum parsimony (MP) tree showed the phylogenetic relationships within this subgenus Passiflora support the classification at the series level. The constructed phylogenic tree also confirmed the divergence of P. foetida from all other species and the closeness of wild and cultivated species. The phylogenetic relationships were consistent with results of morphological assessments. The results of this study indicate that ITS region analysis represents a useful tool for evaluating genetic diversity in Passiflora at the species level.